Analisis Pengaruh Pengungkapan Akuntansi Lingkungan dan Kinerja Lingkungan terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Indeks LQ-45 yang Terdaftar di BEI) - Ethika Ethika; Muhammad Azwari; Resti Yulistia Muslim (Jurnal Kajian Akuntansi dan Auditing, 2019)
This research is to test and analyze the effect of environmental accounting disclosures and environmental performance on firm value in the LQ-45 Index company listed on the Indonesia Stock Exchange for the period 2014-2017. This research is quantitative research. The research sample was 15 companies included in the LQ-45 index, the year of observation from 2014-2017 which had been carried out using a purposive sampling technique. The analysis technique has been carried out using multiple linear regression. The results of the study indicate that the disclosure variables of environmental accounting and environmental performance have a significant effect on firm value. The multiple linear regression model in this study has a value of R2 as 21.5%, which means that the value of the company can be explained using the variable value of disclosure of environmental accounting and environmental performance, where the remaining 79.5% is influenced by other variables outside the model which has been studied.